Evaluasi Perangkat Lunak Electronic Record Management System (ERMS) ARTERI Menggunakan ISO 16175-2:2011 - Gani Nur Pramudyo; Nina Mayesti (Khazanah: Jurnal Pengembangan Kearsipan, 2023)
The aim of the study is to evaluate ERMS software of ARTERI that used the functional requirements of ISO 16175-2: 2011. The researcher chose aspects of search, retrieval, and rendering (disseminate) to evaluate its systems. The study uses a qualitative approach with a review of literature studies. Data were collected by observation and documentation. The findings show ARTERI only meets 10 of 49 functional requirements. Fullfilled functional requirement of ARTERI, includes: 1) Provide a flexible range of functions for locating, accessing, and retrieving records and/or metadata; 2) Allow all records in each level to be searchable; 3) Allow the user to set up a single search request; 4) Never allow a search function to reveal to a user any information; 5) Have integrated search facilities for all levels; 6) Allows users to save and re-use queries; 7) Allows users who are viewing or working with a record; 8) Allows record metadata to be searched; 9) Allows administrators to take a copy of records and reaction; and 10) Store in the metadata any change made. ARTERI needs to be developed, for instance, adding features in any field of content search, automatic search, boolean operators, and improving the user interface for search. Furthermore, the rendering, downloading, and printing features also need to be improved. Finally, the study is limited to certain functional requirements, standards, and applications. Future study needs to consider aspects that have not been discussed or comparisons with certain standards or applications